Controlling the Growth of Local Isolates of Listeria Monocytogenes by Using Some Chemicals Preservatives - Kakey, Shean I.; Ali, Jassim F.; Alzubaidy, Zainab M. (Science Journal of University of Zakho, 2013)
This study include using of some chemical preservative against local isolates of Listeria monocytogenes , the effects of different concentrations of some generally regarded as save (GRAS) preservatives were studied on growth and survival of L. monocytogenes. These preservatives included salts of organic acid (sodium acetate and sodium benzoate) which inhibit growth of the bacterium at (25%) w/v concentration, also the effects of different concentrations of inorganic salt food additives sodium chloride were studied, which inhibit the growth of L. monocytogenes at (15%) w/v concentration . On the other hand the growth and survival of L. monocytogenes at different concentrations of two generally recognized as safe acids (lactic acid and acetic acid ) was determined , the growth of bacterium was completely inhibited at (55mM) concentration of acetic acid and at ( 65mM ) of lactic acid . Controlling of L. monocytogenes by tri-sodium phosphate (TSP) by dipping of artificially contaminated chicken meat in (10%) of TSP for (10) min., significantly reduced the population of the pathogen on the surface of meat to standard safe limit.So the study aimed to determining the effect of some chemical preservatives (acetic acid, lactic acid, sodium benzoate , sodium acetate and sodium chloride) on growth of local isolats of L. monocytogenes which isolated from different food sources in Erbil and Koya city.